PERANAN BANK SAMPAH TERHADAP PENINGKATAN PEREKONOMIAN MASYARAKAT (Studi Empiris : Bank Sampah Kelurahan Bener Yogyakarta) - Robby Prasetyo Utomo; Unggul Priyadi (Universitas Muhammadiyah Mataram, 2024)
This study aims to analyze the management system, empower the community's creative economy through waste recycling, social and economic impacts, as well as the application of circular and sustainable economic concepts at the Waste Bank in Bener Village, Yogyakarta. Based on the results of the research, it can be concluded that the management of the Waste Bank in Bener Yogyakarta Village has successfully implemented the 3R system (Reduce, Reuse, Recycling). The empowerment of the community's creative economy has been actualized through the recycling of waste that has economic value, such as laundry soap from used cooking oil and candles. The Waste Bank also works with wholesale stalls in the area to sell household staples, as well as manage the land around the area as an additional source of income. The social effect benefited by the existence of the Waste Bank in the Bener Village of Yogyakarta is the reduction in the amount of waste produced by the community, which in turn has a positive impact on environmental cleanliness. The economic impact can also be seen from the additional income and business capital for the community. Through this additional income, the community can use it to pay monthly waste bills and meet their daily needs. However, the income from the Waste Bank is still not sufficient to fulfil overall daily needs. A circular and sustainable economy is created through a waste management program in the form of compost and stacked buckets production.